Aluminum fin material
Patent Information
- Application Number
- JP2021066718
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-09
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-04-09
Smart Images

Figure 0007651361000003 
Figure 0007651361000001 
Figure 0007651361000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to an aluminum fin material, and more particularly to an aluminum fin material that is suitable for use in heat exchangers such as air conditioners. [Background technology]
[0002] Heat exchangers are used in a variety of products, including room air conditioners, packaged air conditioners, refrigerated showcases, refrigerators, oil coolers, and radiators. Aluminum and aluminum alloys, which have excellent thermal conductivity, workability, and corrosion resistance, are commonly used as materials for heat exchanger fins. Plate-fin and plate-and-tube heat exchangers have a structure in which the fins are arranged in parallel at close intervals.
[0003] When the surface temperature of a heat exchanger's fins drops below the dew point, condensation forms on them. If the fin surface is not hydrophilic, the contact angle of the condensation increases, causing it to splash into the living environment. Furthermore, when the condensation combines and grows, it forms bridges between adjacent fins, blocking the ventilation passages between the fins and increasing ventilation resistance. To prevent such water splashing and reduce ventilation resistance, for example, Patent Document 1 proposes a technique for applying and forming a hydrophilic coating on the surface of the fins.
[0004] Furthermore, fins are manufactured through processes such as press molding, and processing oil is used during the process, such as press oil. For example, Patent Document 2 discloses an aluminum fin material for heat exchangers in which a corrosion-resistant coating, a hydrophilic coating made of acrylic resin, and a water-soluble lubricant layer made of polyethylene glycol are formed in this order on an aluminum substrate, in consideration of the fact that color bleeding is likely to occur if an excessive amount of press oil is left on the surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 2520308 [Patent Document 2] Japanese Patent Application Laid-Open No. 2013-130320 Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, when processing a heat exchanger, aluminum fin material is heated to volatilize the processing oil applied to it. However, the high temperature and long-term heating causes the coating film on the aluminum plate to deteriorate due to heat, resulting in a decrease in hydrophilicity. Heating is also performed when copper pipes are inserted into the processed aluminum fin material and joined together, and the heating during this joining process also applies excessive heat to the aluminum fin material, reducing the hydrophilicity of the coating film.
[0007] Therefore, an object of the present invention is to provide an aluminum fin material that is excellent in heat resistance and in which the decrease in hydrophilicity due to heating is suppressed. [Means for solving the problem]
[0008] The present invention relates to the following [1] to [5]. [1] An aluminum fin material having an aluminum plate and a coating layer, the coating layer comprising, in order from the aluminum plate side, a hydrophilic coating layer and a lubricating coating layer, the lubricating coating layer comprising a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group, the hydrophilic component having a change in the amount of functional groups that contribute to hydrophilicity of 15% or less before and after heating at 200°C for 10 minutes. [2] The aluminum fin material according to [1], wherein the content of the hydrophilic component is 2.0 to 4000 parts by mass per 100 parts by mass of the resin matrix. [3] The coating amount of the lubricating coating layer is 0.05 to 3.0 mg / dm 2The aluminum fin material according to [1] or [2] above. [4] The aluminum fin material according to any one of [1] to [3] above, wherein the hydrophilic coating layer contains an acrylic acid resin containing a sulfonic acid group and an ether bond. [5] The aluminum fin material according to any one of [1] to [4] above, further comprising a base treatment layer between the aluminum plate and the coating layer. [Effects of the Invention]
[0009] According to the present invention, it is possible to suppress a decrease in hydrophilicity on the surface of the aluminum fin material even when the aluminum fin material is heated during processing of a heat exchanger or when copper tubes are inserted into the aluminum fin material and joined together. As a result, it is possible to provide an aluminum fin material that prevents water splashing and reduces ventilation resistance over a long period of time without losing the initial hydrophilic effect of the aluminum fin material during processing, etc. [Brief explanation of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the configuration of an aluminum fin material. DETAILED DESCRIPTION OF THE INVENTION
[0011] Hereinafter, an embodiment of the aluminum fin material according to the present invention will be described in detail. Note that the symbol "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit.
[0012] <Aluminum fin material> As shown in FIG. 1, an aluminum fin material (hereinafter sometimes simply referred to as "fin material") 10 according to this embodiment has an aluminum plate 1 and a coating layer 2. The coating layer 2 comprises, in order from the aluminum plate 1 side, a hydrophilic coating layer 2b and a lubricating coating layer 2c. The coating layer 2 may further comprise a corrosion-resistant coating layer 2a, and when the corrosion-resistant coating layer 2a is provided, it is located between the aluminum plate 1 and the hydrophilic coating layer 2b. A base treatment layer (not shown) may further be provided between the aluminum plate 1 and the coating layer 2. Furthermore, it is sufficient that at least one surface of the aluminum plate 1 has the above configuration, and both surfaces of the aluminum plate 1 may have the above configuration. Furthermore, when both surfaces of the aluminum plate 1 have the above configuration, the surfaces do not need to have the same configuration.
[0013] The lubricating coating layer 2c includes a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group, and the amount of functional groups that contribute to hydrophilicity of the hydrophilic component changes by 15% or less before and after heating at 200°C for 10 minutes. The lubricating coating layer 2c is a layer intended to lubricate the surface of the fin material and achieve good processability. By providing the lubricating coating layer 2c with the above-described configuration, the hydrophilic effect of the aluminum fin material 10 can be maintained without being lost due to heating or the like, resulting in excellent heat resistance. Furthermore, by adjusting the content of the hydrophilic component relative to the resin matrix in the lubricating coating layer 2c to an appropriate range, good processability can also be achieved. As a result, good processability and properties such as hydrophilicity related to preventing water splashing and reducing ventilation resistance can be achieved and improved without interfering with each other.
[0014] (aluminum plate) The aluminum plate 1 is a concept that includes a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate that has been conventionally used for aluminum fin materials can be used. As the aluminum plate 1, 1000 series aluminum as specified in JIS H 4000:2014 is preferred because of its excellent thermal conductivity and workability. More specifically, aluminum alloys of alloy numbers 1050, 1070, and 1200 are more preferred. However, the above description does not in any way exclude the use of 2000 series to 9000 series aluminum alloys or other aluminum plates as the aluminum plate.
[0015] The aluminum plate 1 has a thickness that is appropriately determined depending on the application and specifications of the fin material. For fin materials for heat exchangers, the thickness is preferably 0.08 mm or more, and more preferably 0.1 mm or more, from the viewpoint of fin strength, etc. On the other hand, the thickness is preferably 0.3 mm or less, and more preferably 0.2 mm or less, from the viewpoint of workability into fins and heat exchange efficiency, etc.
[0016] (lubricating coating layer) The lubricating coating layer 2c is a layer intended to obtain good processability by increasing the lubricity of the fin material surface. Specifically, by containing a resin that increases lubricity, the coefficient of friction of the fin material surface is reduced, making it lubricated, and improving press formability when processing the fin material into a fin.
[0017] The lubricating coating layer 2c contains a resin matrix and a hydrophilic component. The resin matrix is a resin component that forms the base composition of the lubricating coating layer 2c. For example, the content of the resin matrix in the lubricating coating layer 2c is preferably 60% by mass or more relative to the total amount of the components that make up the lubricating coating layer 2c. There is no particular upper limit to the content of the resin matrix, but it is, for example, 70% by mass or less.
[0018] The resin matrix contains polyethylene glycol (PEG) as a main component. In this specification, polyethylene glycol (PEG) also includes modified compounds thereof. The modified polyethylene glycol compound is a modified polyethylene glycol having one or more functional groups selected from the group consisting of a urethane bond, an ester bond, and an ether bond in its structure. Among these, modified polyethylene glycols having a urethane bond in their structure are preferred because they have functional groups with excellent elongation.
[0019] By including a resin matrix containing polyethylene glycol as a main component, when combined with a specific hydrophilic component described below, deterioration of hydrophilic function due to heat can be suppressed, resulting in good heat resistance.
[0020] The resin constituting the resin matrix may be polyethylene glycol alone, or may contain other resins in addition to polyethylene glycol. Examples of other resins include resins having hydrophilic groups, such as hydroxyl groups, carboxyl groups, sulfonic acid groups, and polyether groups.
[0021] Resins having hydroxyl groups other than polyethylene glycol (PEG) include polyvinyl alcohol (PVA). Resins having carboxyl groups include polyacrylic acid (PAA). Resins having both hydroxyl and carboxyl groups include carboxymethyl cellulose (CMC). Resins having sulfonic acid groups include sulfoethyl acrylate. In addition to these, copolymers of two or more types of monomers having hydrophilic groups can also be used.
[0022] The resin matrix may contain resins other than polyethylene glycol, but "containing polyethylene glycol as a main component" means that the proportion of polyethylene glycol relative to the total amount of polyethylene glycol and other resins is 60% by mass or more. When the polyethylene glycol contains two or more types of polyethylene glycol with different molecular weights or structures, the total proportion of these polyethylene glycols may be 60% by mass or more. The proportion of polyethylene glycol relative to the total amount of polyethylene glycol and other resins is preferably 70% by mass or more, more preferably 80% by mass or more, and the upper limit may be 100% by mass, i.e., the resin may be composed solely of polyethylene glycol.
[0023] The hydrophilic component contained in the lubricating coating layer 2c contains at least one of a sulfonic acid group and an ester group. This hydrophilic component exhibits a change in the amount of functional groups that contribute to hydrophilicity of 15% or less before and after heating at 200°C for 10 minutes. The inclusion of such a hydrophilic component provides hydrophilicity with excellent heat resistance.
[0024] Examples of hydrophilic components include sulfonic acid acrylic compounds, phosphate ester compounds, acrylic compounds, etc. However, as described above, the change in the amount of functional groups that contribute to hydrophilicity before and after heating at 200°C for 10 minutes must be 15% or less.
[0025] The change in the amount of functional groups that contribute to hydrophilicity before and after heating at 200° C. for 10 minutes should be 15% or less, preferably 10% or less, and more preferably 5% or less. In this specification, the change in the amount of functional groups that contribute to hydrophilicity can be measured using a Fourier transform infrared spectrophotometer.
[0026] From the viewpoint of obtaining good hydrophilicity, the content of the hydrophilic component per 100 parts by mass of the resin matrix is preferably 2.0 parts by mass or more, more preferably 5.0 parts by mass or more, even more preferably 6.0 parts by mass or more, even more preferably 8.0 parts by mass or more, and particularly preferably 10 parts by mass or more. From the viewpoint of lubricity for obtaining good processability, the content of the hydrophilic component is preferably 6,000 parts by mass or less, more preferably 5,000 parts by mass or less, even more preferably 4,000 parts by mass or less, and even more preferably 3,000 parts by mass or less.
[0027] In addition to the above, the lubricating coating layer 2c may contain other optional components within the scope of the present invention, such as various water-based solvents and paint additives for improving the coatability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, antifoaming agents, antifouling agents, anti-rust agents, antibacterial agents, anti-fungal agents, etc. One type of these paint additives may be contained, or two or more types may be contained.
[0028] For example, silicone components are an example of antifouling agents. Silicone components have low surface free energy and are thought to have low adhesion to substances. Therefore, by including silicone components, adhesion of contaminants, mainly oily components, can be suppressed.
[0029] The silicone component is a polymer of a silicon compound, and is a compound having a siloxane bond as a skeleton. The silicone component preferably contains a modified polydimethylsiloxane derivative having one or more functional groups selected from polyether groups, epoxy groups, methacrylic groups, amino groups, phenyl groups, hydrogen groups, and hydroxyl groups in its structure, because it has particularly high dispersibility in paints and high fixability in resin films, and more preferably contains a modified polydimethylsiloxane derivative having one or more functional groups selected from the group consisting of epoxy groups, methacrylic groups, phenyl groups, and hydrogen groups in its structure. Silicones containing long-chain alkyl groups are also preferred. Such modified polydimethylsiloxane derivatives and silicones containing long-chain alkyl groups can be nonionic, anionic, or cationic, with nonionic being preferred.
[0030] The lubricating coating layer 2c can be formed by applying a resin coating containing a resin matrix and a hydrophilic component onto the hydrophilic coating layer 2b, and then solidifying it by drying or the like.
[0031] The coating amount of the lubricating coating layer 2c is 0.05 mg / dm from the viewpoint of obtaining sufficient lubricity and heat-resistant hydrophilicity. 2 More than 0.1 mg / dm 2 More preferably, 0.2 mg / dm 2 On the other hand, from the viewpoint of suppressing a decrease in hydrophilicity due to some of the components constituting the lubricating coating layer 2c remaining on the surface when the surface of the fin material is wetted with water, the coating amount is set to 3.0 mg / dm 2 Less than 1.5 mg / dm 2 Less than 1.0 mg / dm is more preferable. 2 The following is even more preferred:
[0032] The thickness of the lubricating coating layer 2c is not particularly limited, but from the viewpoint of obtaining lubricity and heat-resistant hydrophilicity, the density of the coating layer is set to 1 g / cm 3 Assuming this, the thickness is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.02 μm or more. Furthermore, from the viewpoint of obtaining good coating workability when forming the lubricating coating layer 2c, the thickness is preferably 0.3 μm or less, more preferably 0.15 μm or less, and even more preferably 0.1 μm or less. The thickness of the lubricating coating layer 2c can be adjusted by the concentration of the coating composition used to form the lubricating coating layer 2c, the selection of the bar coater number, and the like.
[0033] (Hydrophilic film layer) The hydrophilic coating layer 2b is a coating layer that imparts hydrophilicity to the surface of the fin material, and contains a conventionally known hydrophilic resin. The hydrophilic resin may contain one type of resin or two or more types of resins as long as it has a hydrophilic group. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.
[0034] Examples of those having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Examples of those having a carboxyl group include polyacrylic acid (PAA). Examples of those having a hydroxyl group and a carboxyl group include carboxymethyl cellulose (CMC). Examples of those having a sulfonic acid group include sulfoethyl acrylate. Examples of those having a polyether group include polyethylene glycol (PEG).
[0035] Among these, from the viewpoint of more suitably exhibiting the desired hydrophilicity even when the lubricating coating layer 2c is formed on the surface of the hydrophilic coating layer 2b, the hydrophilic resin is preferably one containing a sulfonic acid group or a polyether group, i.e., one containing an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic acid resin containing a sulfonic acid group and an ether bond.
[0036] The acrylic acid resin containing sulfonic acid and an ether bond is an acrylic acid resin containing an unsaturated double bond group and a sulfonic acid group, and examples thereof include polyvinyl ether-sulfonic acid acrylic copolymer, benzyl ether-sulfonic acid acrylic copolymer, etc. However, the acrylic acid resin containing sulfonic acid and an ether bond is not limited to these.
[0037] In addition to the above, the hydrophilic resin may also be a copolymer of two or more types of monomers having a hydrophilic group. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, or the like, and the method of arranging the monomers is not particularly limited.
[0038] It is preferable that the hydrophilic coating layer 2b further contains a surfactant in addition to the hydrophilic resin. This allows for both better hydrophilicity and processability due to the lubricating coating layer 2c formed on the hydrophilic coating layer 2b. This is thought to be due to the surface-exposure effect of the surfactant.
[0039] Any of anionic, cationic and nonionic surfactants can be used, but anionic surfactants are preferred from the viewpoint of ease of dispersion in the hydrophilic coating layer.
[0040] From the viewpoint of improving hydrophilicity, it is more preferable that the anionic surfactant contains at least one compound selected from the group consisting of polyoxyethylene alkyl ether phosphate esters, polyoxyethylene alkyl ether sulfates, and polyoxyethylene alkyl sulfosuccinates.
[0041] The hydrophilic coating layer 2b can be formed by applying a resin paint containing a hydrophilic resin onto a layer that will serve as an underlying layer such as the corrosion-resistant coating layer 2a, and then solidifying the paint by drying or the like. The amount of hydrophilic resin attached to the hydrophilic film is 0.2 mg / dm in order to obtain sufficient hydrophilicity. 2 More than 1 mg / dm 2 More than 2 mg / dm is more preferable. 2 Furthermore, from the viewpoint of preventing the hydrophilic resin from eluting when the surface of the fin material is wetted with water, thereby inhibiting the effect of the lubricating coating layer 2c, the amount of hydrophilic resin attached is set to 30 mg / dm 2 Less than 20 mg / dm 2 Less than 15 mg / dm is more preferable. 2 The following is even more preferred:
[0042] In addition to the hydrophilic resin and surfactant, the hydrophilic coating layer 2b may contain other optional components within the scope of the present invention, such as various aqueous solvents and paint additives for improving the coatability, workability, and physical properties of the coating layer. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, anti-foaming agents, rust inhibitors, antibacterial agents, anti-fungal agents, etc. These paint additives may be contained alone or in combination of two or more.
[0043] The thickness of the hydrophilic coating layer 2b is not particularly limited, but the density of the hydrophilic coating layer 2b is preferably 1 g / cm 3 Assuming this, in order to obtain good hydrophilicity, the thickness is preferably 0.02 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more. In order to obtain good coating workability when forming the hydrophilic coating layer 2b, the thickness is preferably 3 μm or less, more preferably 2 μm or less, and even more preferably 1.5 μm or less. The thickness of the hydrophilic coating layer 2b can be adjusted by the concentration of the coating composition used to form the hydrophilic coating layer 2b, the selection of the bar coater number, and the like.
[0044] The total thickness of the hydrophilic coating layer 2b and the lubricating coating layer 2c is preferably 5 μm or less in order to prevent a decrease in the heat exchange efficiency of the fin material.
[0045] (Corrosion-resistant coating layer) The corrosion-resistant coating layer 2a may be provided primarily to enhance the corrosion resistance of the aluminum plate, and is preferably formed between the aluminum plate 1 and the hydrophilic coating layer 2b, and more preferably contains a hydrophobic resin. When a substrate treatment layer (not shown) is formed on the surface of the aluminum plate 1, the corrosion-resistant coating layer 2a is formed on the substrate treatment layer. The corrosion-resistant coating layer 2a can be formed, for example, by applying a resin paint containing a hydrophobic resin onto the aluminum plate 1 or the surface treatment layer, and then solidifying it by drying or the like.
[0046] The corrosion-resistant coating layer 2a makes it difficult for moisture such as condensation water, oxygen, ionic species such as chloride ions, and the like to penetrate into the aluminum plate 1, thereby suppressing corrosion of the aluminum plate 1 and the production of aluminum oxides that cause odors.
[0047] The hydrophobic resin in the corrosion-resistant coating layer 2a may be a conventionally known resin, such as polyester, polyolefin, epoxy, urethane, or acrylic resins, or a mixture of two or more of these resins.
[0048] In addition to the above, the corrosion-resistant coating layer 2a may contain other optional components within the range that does not impair the effects of the present invention. Optional components include, for example, various water-based solvents and paint additives for improving paintability, workability, and physical properties of the coating. Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, anti-foaming agents, rust inhibitors, antibacterial agents, anti-fungal agents, etc. One type of these paint additives may be contained, or two or more types may be contained.
[0049] The amount of the hydrophobic resin attached to the corrosion-resistant coating layer 2a is not particularly limited, but from the viewpoint of imparting sufficient corrosion resistance to the aluminum plate 1, it is preferred that the amount be 1.0 mg / dm 2 More than 3.0 mg / dm 2 On the other hand, from the viewpoint of suppressing a decrease in the heat exchange efficiency of the fins, the amount of hydrophobic resin attached is preferably 50 mg / dm 2 Less than 40 mg / dm 2 The following is more preferred: The thickness of the corrosion-resistant coating layer 2a is preferably 0.05 μm or more from the viewpoint of obtaining good corrosion resistance, and the thickness is preferably 4 μm or less from the viewpoints of good film-forming properties, reducing defects such as cracks, and keeping the heat transfer resistance of the corrosion-resistant coating layer 2a low, thereby obtaining good heat exchange efficiency of the fin. The thickness of the corrosion-resistant coating layer 2a and the amount of hydrophobic resin applied can be adjusted by selecting the concentration of the coating composition used to form the corrosion-resistant coating layer 2a and the bar coater number.
[0050] (Base treatment layer) If desired, a substrate treatment layer may be provided between the aluminum plate 1 and the corrosion-resistant coating layer 2a. By providing the undercoat treatment layer, the corrosion resistance of the aluminum plate 1 can be improved, and the adhesion between the aluminum plate 1 and the corrosion-resistant coating layer 2a can be improved.
[0051] Any known undercoat treatment layer can be used as long as it can impart corrosion resistance to the aluminum plate 1. For example, a layer made of an inorganic oxide or an inorganic-organic composite compound can be used. The inorganic material constituting the inorganic oxide or inorganic-organic composite compound preferably has chromium (Cr), zirconium (Zr) or titanium (Ti) as the main component.
[0052] The layer made of an inorganic oxide that serves as the undercoat treatment layer can be formed, for example, by subjecting the aluminum plate 1 to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic phosphate treatment, etc. However, the type of inorganic oxide is not limited to those formed by these treatments.
[0053] The layer made of an inorganic-organic composite compound that serves as the undercoat treatment layer can be formed, for example, by subjecting the aluminum plate 1 to a coating type chromate treatment or a coating type zirconium treatment. A specific example of such an inorganic-organic composite compound is an acrylic-zirconium composite.
[0054] The thickness of the undercoat treatment layer is not particularly limited and may be set appropriately, but the amount of adhesion per unit area should be 1 to 100 mg / m in terms of metal (Cr, Zr, Ti) equivalent. 2 The thickness is preferably 1 to 100 nm. The deposition amount and film thickness of the undercoat treatment layer can be adjusted by adjusting the concentration of the chemical conversion treatment solution used to form the undercoat treatment layer and the film formation treatment time.
[0055] Before forming the primer layer, the surface of the aluminum plate 1 may be degreased in advance using an alkaline degreasing solution, which improves the reactivity of the primer treatment and also improves the adhesion of the formed primer layer.
[0056] (Characteristics of aluminum fin material) The aluminum fin material 10 according to this embodiment can suppress a decrease in hydrophilicity on the fin material surface even after heating during processing, inserting a copper pipe, etc. Furthermore, by setting the content of the hydrophilic component relative to the resin matrix in the lubricating coating layer 2c within an appropriate range, good processability can also be achieved.
[0057] The workability of the fin material 10 due to the lubricating coating layer 2c can be evaluated by the coefficient of friction. The static friction coefficient measured by a horizontal linear reciprocating sliding method after applying processing oil to the surface of the fin material 10 is preferably 0.20 or less, more preferably 0.15 or less, and even more preferably 0.10 or less. The lower limit is not particularly limited, but is usually 0.01 or more. When no processing oil is applied to the surface of the fin material 10, the static friction coefficient measured by a horizontal linear reciprocating sliding method is preferably 0.20 or less, more preferably 0.17 or less, even more preferably 0.15 or less, and even more preferably 0.12 or less. The lower limit is not particularly limited, but is usually 0.01 or more.
[0058] The heat resistance of the fin material 10 with respect to hydrophilicity can be evaluated by heating the fin material 10 and then dropping pure water onto its surface, and measuring the contact angle. The contact angle of pure water is measured using a contact angle meter. The surface of the fin material 10 is coated with processing oil, heated at 200°C for 10 minutes, and then returned to room temperature. After that, approximately 0.5 μL of pure water is dropped onto the surface. The contact angle of the droplet (pure water) is preferably 22° or less, more preferably 20° or less, and even more preferably 15° or less. The lower limit is not particularly limited, but is usually 5° or more.
[0059] In addition to the heat resistance related to the hydrophilicity of the fin material 10, the durability when the fin material 10 is used in a heat exchanger can be evaluated by the contact angle of pure water after undergoing a dry-wet cycle. The surface of the fin material 10 is coated with processing oil, heated at 200°C for 10 minutes, and returned to room temperature. Each cycle consists of the steps (i) and (ii) below, and the fin material 10 is subjected to 14 cycles of these steps. The temperature is then returned to room temperature, and approximately 0.5 μL of pure water is dropped onto the surface of the fin material 10. The contact angle of the droplet (pure water) is preferably 22° or less, more preferably 20° or less, and even more preferably 19° or less. While there is no particular lower limit, it is typically 5° or more. (i) The fin material is exposed to ion-exchanged water at a flow rate of 0.1 mL / min for 8 hours. (ii) Then dry at 80°C for 16 hours.
[0060] The thickness of the fin material 10 varies depending on the application and is not particularly limited, but when used in a heat exchanger, for example, the thickness is preferably 0.08 mm or more, more preferably 0.1 mm or more, from the viewpoint of strength that can withstand processing. Also, from the viewpoints of processability and heat exchange efficiency, the thickness is preferably 0.3 mm or less, more preferably 0.2 mm or less.
[0061] <Method of manufacturing aluminum fin material> An example of a manufacturing method for the aluminum fin material 10 according to this embodiment will be described, but the present invention is not limited to this embodiment, and the material can also be manufactured by other manufacturing methods as long as the effects of this embodiment are not hindered.
[0062] After forming a corrosion-resistant coating layer 2a on an aluminum plate 1 by a known method, a coating composition containing a hydrophilic resin is applied and dried to form a hydrophilic coating layer 2b. Before forming the corrosion-resistant coating layer 2a, a primer layer may be formed as desired. Next, a resin coating containing a resin matrix and a hydrophilic component is applied onto the hydrophilic coating layer 2b and dried to form a lubricating coating layer 2c.
[0063] The resin matrix contained in the resin coating used to form the lubricating coating layer 2c contains polyethylene glycol as a main component. The hydrophilic component contained in the resin coating contains at least one of a sulfonic acid group and an ester group. The amount of functional groups contributing to hydrophilicity in the hydrophilic component changes by 15% or less before and after heating at 200°C for 10 minutes.
[0064] When forming the hydrophilic coating layer 2b, by including an acrylic acid resin containing a sulfonic acid group and an ether bond in the coating composition, the desired hydrophilicity can be more suitably exhibited even if a lubricating coating layer 2c is formed on the surface of the hydrophilic coating layer 2b.
[0065] The lubricating coating layer 2c, the hydrophilic coating layer 2b, and the corrosion-resistant coating layer 2a are formed by preparing a coating composition for each coating layer, applying it to the object to be coated using a bar coater or roll coating method, and then baking it. In particular, if the aluminum plate 1 is in a coiled form, it is preferable from the viewpoint of productivity to use a roll coater or the like to continuously perform degreasing, coating, heating, winding, etc. The baking temperatures for the lubricating coating layer 2c, the hydrophilic coating layer 2b, and the corrosion-resistant coating layer 2a can be set depending on the components of the resins and the like used, and are preferably in the range of 120 to 270°C, for example. [Example]
[0066] The present invention will be explained in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and modifications can be made within the scope of the invention, and all such modifications are included in the technical scope of the present invention.
[0067] Example 1 The aluminum plate used was a 0.1 mm thick aluminum plate of alloy number 1070 specified in JIS H 4000:2014. A primer layer was formed on one surface of the aluminum plate by phosphate chromate treatment. The coating weight of the primer layer was 20 mg / dm 2 It was. Next, a coating composition containing an epoxy resin was applied with a bar coater and baked at 200°C to form a corrosion-resistant coating layer. The coating amount of the corrosion-resistant coating layer was 7.5 mg / dm 2 It was decided. Next, a resin composition containing a sulfonic acid group-containing ether-based acrylic compound as a main component as a hydrophilic resin was applied to the surface of the corrosion-resistant coating layer using a bar coater. The coating was then baked at 220°C to form a hydrophilic coating layer. The coating amount of the hydrophilic coating layer was 6 mg / dm 2 It was decided. Finally, a resin coating containing modified polyethylene glycol as the resin matrix (A) and a sulfonate acrylic compound as the hydrophilic component (B) was applied to the surface of the obtained hydrophilic coating layer using a bar coater, and baked at 160°C to form a lubricating coating layer, thereby obtaining an aluminum fin material. The amount of sulfonate acrylic compound added per 100 parts by mass of modified polyethylene glycol was 6 parts by mass. The coating mass of the lubricating coating layer was 1.0 mg / dm 2 It was decided.
[0068] (Examples 2 to 15) In forming the lubricating coating layer, the amount of sulfonic acid acrylic compound, which is the hydrophilic component (B), added to 100 parts by mass of modified polyethylene glycol, which is the resin matrix (A), was changed to the amount shown in Table 1. Aluminum fin material was obtained in the same manner as in Example 1.
[0069] Example 16 In forming the lubricating coating layer, aluminum fin material was obtained in the same manner as in Example 1, except that a phosphate ester compound was added as the hydrophilic component (B) in the amount shown in Table 1 instead of the sulfonic acid acrylic compound.
[0070] (Comparative Example 1) An aluminum fin material was obtained in the same manner as in Example 1, except that the sulfonic acid acrylic compound, which is the hydrophilic component (B), was not added in forming the lubricating coating layer.
[0071] (Comparative Example 2) Aluminum fin material was obtained in the same manner as in Example 1, except that in forming the lubricating coating layer, modified polyethylene glycol, which serves as the resin matrix (A), was not used, and a layer consisting only of a sulfonic acid acrylic compound, which serves as the hydrophilic component (B), was formed.
[0072] (Comparative Example 3) In forming the lubricating coating layer, aluminum fin material was obtained in the same manner as in Example 1, except that, as the hydrophilic component (B), instead of the sulfonic acid acrylic compound, a polyacrylic acid compound containing an ester group but not a sulfonic acid group was added in the amount shown in Table 1.
[0073] Comparative Example 4 Aluminum fin material was obtained in the same manner as in Example 1, except that in forming the hydrophilic coating layer, a sulfonate acrylic compound was used instead of the resin composition containing the sulfonate group-containing ether acrylic compound, and in forming the lubricating coating layer, the sulfonate acrylic compound, which is the hydrophilic component (B), was not added.
[0074] Example 17 When forming the lubricating film layer, the film amount of the lubricating film layer is 0.2 mg / dm 2 An aluminum fin material was obtained in the same manner as in Example 1, except that:
[0075] (Examples 18 to 31) In forming the lubricating coating layer, the amount of sulfonic acid acrylic compound, which is the hydrophilic component (B), added relative to 100 parts by mass of modified polyethylene glycol, which is the resin matrix (A), was changed to the amount shown in Table 2. An aluminum fin material was obtained in the same manner as in Example 17.
[0076] (Comparative Example 5) An aluminum fin material was obtained in the same manner as in Example 17, except that the sulfonic acid acrylic compound, which is the hydrophilic component (B), was not added in forming the lubricating coating layer.
[0077] (Comparative Example 6) Aluminum fin material was obtained in the same manner as in Example 17, except that in forming the lubricating coating layer, modified polyethylene glycol, which serves as the resin matrix (A), was not used, and a layer consisting only of a sulfonic acid acrylic compound, which serves as the hydrophilic component (B), was formed.
[0078] (Amount of change in functional groups of hydrophilic components) The hydrophilic components contained in the lubricating coating layer of the aluminum fin material were measured using a Fourier transform infrared spectrophotometer (NICOLET iZ10, manufactured by Thermo Fisher Scientific) to determine the change in the amount of functional groups that contribute to hydrophilicity before and after heating at 200°C for 10 minutes. Specifically, the 1510 cm -1 and a peak around 2900 cm indicating functional groups that do not contribute to hydrophilicity. -1 The intensity ratio of the peak near the peak was taken as the amount of functional group A in the component, and the amount of functional group A in the component before heating was taken as standard (1). A determination was made as to whether the amount of functional group A in the component after heating at 200°C for 10 minutes had changed by 15% or less (0.85 or more). The results are shown in Tables 1 and 2 under "Change in functional groups (%) in lubricating coating layer (B)."
[0079] (Evaluation: Workability) The obtained aluminum fin material was evaluated for workability due to the lubricating coating layer using the coefficient of friction as described below. The surface of the fin material was oiled with processing oil and the static friction coefficient was measured using a horizontal linear reciprocating sliding method (TS-501 model, manufactured by Kyowa Interface Science Co., Ltd.). The evaluation criteria are as follows, and the results are shown in "Friction coefficient with oiling" in Tables 1 and 2. Note that blanks mean that the measurement was not performed. A Very good (pass): Static friction coefficient is 0.15 or less B Good (pass): Static friction coefficient is over 0.15 and 0.20 or less C Bad (fail): Static friction coefficient is greater than 0.20
[0080] Regarding the workability of the lubricating coating layer, the static friction coefficient was measured in the same manner as above, except that no processing oil was applied to the surface of the fin material. The evaluation criteria are as follows, and the results are shown in "Friction coefficient without oil application" in Tables 1 and 2. Note that blanks indicate that no measurement was performed. A Very good (pass): Static friction coefficient is 0.15 or less B Good (pass): Static friction coefficient is over 0.15 and 0.20 or less C Bad (fail): Static friction coefficient is greater than 0.20
[0081] (Evaluation: Heat resistance) The obtained aluminum fin material was evaluated for heat resistance related to hydrophilicity as follows by measuring the contact angle when pure water was dropped on its surface. The surface of the fin material was coated with processing oil and heated at 200°C for 10 minutes. After returning to room temperature, approximately 0.5 μL of pure water was dropped onto the surface. The contact angle of the droplet (pure water) was measured using a contact angle measuring instrument (Kyowa Interface Science Co., Ltd., CA-05 model). The evaluation criteria are as follows, and the results are shown in "Contact angle after heating" in Tables 1 and 2. Note that blanks indicate that no measurement was performed. A Very good (pass): Contact angle is 15° or less B Good (pass): Contact angle is greater than 15° and less than 22° C Bad (fail): Contact angle is greater than 22°
[0082] (Rating: Durability) The durability of the fin material when used in a heat exchanger was evaluated as follows based on the contact angle of pure water after undergoing a dry-wet cycle. The surface of the fin material was coated with processing oil, heated at 200°C for 10 minutes, and returned to room temperature. Next, (i) the fin material was exposed to ion-exchanged water at a flow rate of 0.1 mL / min for 8 hours, and (ii) subsequently dried at 80°C for 16 hours. This process was repeated 14 times. After that, the temperature was returned to room temperature, and approximately 0.5 μL of pure water was dropped onto the surface of the fin material. The contact angle of the droplet (pure water) was measured using a contact angle meter (Kyowa Interface Science Co., Ltd., Model CA-05). The evaluation criteria were as follows, and the results are shown in Tables 1 and 2 under "Contact angle after dry-wet cycle." Note that blanks indicate that no measurement was performed. A Very good (pass): Contact angle is 20° or less B Good (pass): Contact angle is greater than 20° and less than 22° C Bad (fail): Contact angle is greater than 22°
[0083] [Table 1]
[0084] [Table 2]
[0085] From the above results, it was found that by including a resin matrix containing polyethylene glycol in the lubricating coating layer and a hydrophilic component containing at least one of sulfonic acid groups and ester groups and with a small change in the amount of functional groups before and after heating, the decrease in hydrophilicity due to heating is suppressed, and an aluminum fin material with excellent heat resistance can be obtained. If the change in the amount of functional groups in the hydrophilic component before and after heating is large, good hydrophilicity after heating cannot be achieved, even if the hydrophilic component contains sulfonic acid groups or ester groups, as shown in Comparative Example 3. Furthermore, by setting the content of the hydrophilic component relative to the resin matrix in the lubricating coating layer within an appropriate range, good processability can also be achieved. [Explanation of symbols]
[0086] 1 aluminum plate 2. Coating layer 2a Corrosion-resistant coating layer 2b Hydrophilic film layer 2c Lubricating film layer 10 Aluminum fin material (fin material)
Claims
1. The present invention has an aluminum plate and a coating layer. The coating layer includes, in order from the aluminum plate side, a hydrophilic coating layer and a lubricating coating layer, the lubricating coating layer includes a resin matrix containing polyethylene glycol as a main component, and a hydrophilic component containing a sulfonic acid acrylic compound or a phosphate ester compound, The aluminum fin material, wherein the hydrophilic component exhibits a change in the amount of functional groups that contribute to hydrophilicity of 15% or less before and after heating at 200°C for 10 minutes.
2. The aluminum fin material according to claim 1, wherein the content of the hydrophilic component per 100 parts by mass of the resin matrix is 2.0 to 4000 parts by mass.
3. The coating amount of the lubricating coating layer is 0.05 to 3.0 mg / dm 2 The aluminum fin material according to claim 1 or claim 2.
4. The aluminum fin material according to any one of claims 1 to 3, wherein the hydrophilic coating layer contains an acrylic resin containing a sulfonic acid group and an ether bond.
5. The aluminum fin material according to any one of claims 1 to 4, further comprising a base treatment layer between the aluminum plate and the coating layer.
Citation Information
Patent Citations
Organic hydrophilic coating composition and aluminum material for heat exchanger having hydrophilic film
JP2002275407A
Fin material made of aluminum for heat exchanger and fin
JP2003286583A
Hydrophilic member and method of manufacturing fin material for heat exchanger
JP2010155441A
Aluminum fin material for heat exchanger
JP2013130320A
Hydrophilic surface treatment agent, hydrophilic surface treatment bath, and surface treatment method for aluminum material
JP2520308B2